Intercultural Communicative Competence : Reflecting About the Stereotypes Regarding Venezuelan Migrants. (2020)
ABSTRACT: This project report presents the development of a learning guide that intends to explore the Intercultural communicative competence as the means to make the students of tenth grade in a public school reflect on the ideas and assumptions regarding Venezuelan migrants. The activities include the reading of two biographies, one from a Colombian singer and the other from a Venezuelan singer that migrated at a certain point in their lives. While analyzing the biographies and producing their own texts, learners will reflect on the concept of migration, stereotypes and other ideas they have of one another at the same time as they learn more about each other.